1975
DOI: 10.1055/s-0028-1097804
|View full text |Cite
|
Sign up to set email alerts
|

2α, 3α–DIHYDROXYOLEAN–12–EN–28–OIC ACID FROMHOLOPTELEA INTEGRIEOLIAHEARTWOOD

Abstract: 2a, 3a-Dihydroxyolean-12-en-28-oic acid has been isolated from Holoptelea integrifolia heartwood and its structure elt~cidated by physico-chemical methods and comparison with synthetic sample. Holoptelea integrifolia PLANCH. syn. Ulmzrs integrifolia ROXB. (Lllmaceae) locally known as Chilbil, is a roadside tree distributed throughout the greater part of India [I]. T h e bark yields friedelin and friedelin-3fi-01 and the leaves yield hexacosanol, octacosanol, fi-sitosterol and fi-amyrin [2]. In pursuance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…2 R'=R2=ot-OH, R3=H 3 R1=3-OAc, R2=ot-OAc, R3=H 4 R1 = ß-OH, R2=ct-OH, R3=H 5 R1=a-OAc, R^-OAc, R3=OH Compound 2 formed an acetonide (7), and its eims gave peaks at mlz 510 [M]+ (1%), 464 [ -H -COOH]+ (1%), 452 [M-MeCOMe}+ (1%), 406 (5%), 248 (100%), and 203 (48%). Formation of an acetonide supported the cis configuration or the diequatorial conformation of the hydroxyl groups (8). Acetylation of compound 2 yielded the product as a gum.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…2 R'=R2=ot-OH, R3=H 3 R1=3-OAc, R2=ot-OAc, R3=H 4 R1 = ß-OH, R2=ct-OH, R3=H 5 R1=a-OAc, R^-OAc, R3=OH Compound 2 formed an acetonide (7), and its eims gave peaks at mlz 510 [M]+ (1%), 464 [ -H -COOH]+ (1%), 452 [M-MeCOMe}+ (1%), 406 (5%), 248 (100%), and 203 (48%). Formation of an acetonide supported the cis configuration or the diequatorial conformation of the hydroxyl groups (8). Acetylation of compound 2 yielded the product as a gum.…”
mentioning
confidence: 89%
“…The similarity in chemical shifts of the seven methyl groups in the 'H-nmr spectrum of 2 and its diacetate suggested that the two oxygen functionalities in the molecule were both a. If the hydroxyl groups were ß, the chemical shifts of the C-24 and C-25 methyls of 2 would appear downfield in comparison to those of the diacetate (5,8).…”
mentioning
confidence: 99%
“…The major (10 g) and highest melting methylester was, of course, the rare triterpene acid already reported [3]. The location of the two hydroxyl groups in rings A and/or B is indicated by the peaks at m/e 262 and rnle 223 corresponding to fragments 'a' and 'g' [6].…”
mentioning
confidence: 69%
“…While continuing the investigations on different parts of H. integrifolia, a systematic chemical examination of its heartwood was undertaken. Along with the report [3] of isolation and structure elucidation of a rare triterpenoid, 2a, 3a-dihydroxyolean-12-en-28-oic acid, the presence of some other constituents in the heartwood had been indicated. The isolation and characterisation of these constituents is described here.…”
mentioning
confidence: 99%
“…6 g of E was treated with CHzNz, after purification the yields of esters were methyl ursolate (3.5 g), 2a,3a dihydroxy-urs-12-en-28-methyl ester (50 mg) (Misra et al, 1975), 2a,3a dihydroxy-olean-12-en-28 methyl ester (10 mg) (Misra et al, 1975). 2a,3P dihydroxy-urs-12-en-28-methyl ester (100 mg) (Caputo et al, 1974), 2a,3~dihydroxy-olean-l2-en-28-methyl ester (50mg) (Tandon et al, 1980) and 2a,3a, 23 trihydroxy-urs-12-en-28-methyl ester (8 mg) (Tandon et al, 1980 D was washed with pyridine and the solution filtered and analysed by HPLC: five sugars were identified raffinose (lo%), saccharose (5.2%), glucose (l8%), galactose (2%) and fructose (18%).…”
Section: Methodsmentioning
confidence: 99%